Pengaruh Penggunaan Kombucha Terhadap Kandungan Protein Kasar Dan Serat Kasar Pada Fermentasi Eceng Gondok (Eichornia crassipes) [The Effect Of Using Kombucha On Crude Protein And Crude Fiber Contents In Water Hyacinth (Eichornia crassipes) Fermentation] - Agustono Agustono; Salim Hidayat; Widya Paramita L (Jurnal Ilmiah Perikanan dan Kelautan)
Abstract Water hyacinth (Eichornia crassipes) is a one of the feed materials from the green plants a potential. Howefer, the water hyacinth are low of protein and high fiber contents. Therefore, there should be efforts intentionally done to increase the leaf protein. One the ways to raise water hyacinth nutrient is performing biologically fermentation by using microbes. The Kombucha organism is a symbiotic colony of yeast’s and bacteria that composed by strong membrane that covers gelatinous mass. Kombucha microorganism is living together with permeate the tea drink. The objective of this research is to know the effect of Kombucha to increased crude protein and decreased crude fiber contents in water hyacinth fermentation. The advantage of the research is to provide information regarding a Kombucha dosage which is required to enhance crude protein and reduce crude fiber content on water hyacinth fermentation. The research used water hyacinth as substrate and Kombucha as fermentor. Kombucha dosaged used here were P0 (0%), P1 (7,5%), P2 (15%) and P3 (22,5%). The fermentation took place 7 days and then proceeded with proximate analysis. Variables observed consisted of crude protein and crude fiber contents after being fermented using Kombucha. The result showed that Kombucha that was used for fermenting water hyacinth, could increase the crude protein content from 13,3040 % (P0) to 15,9972% (P3) and not significantly reduce the crude fiber. The Kombucha dosage at 7,5% (P1) was most effective for fermenting the water hyacinth.